Comparative Studies on the Healing Rant of Blazes Tapped by ’Cup Lip’ Method (Channels) and ’Rill method’ (Rills) in Pinus roxrurghii - Chaudhari, D. C.; Uniyal, D. N.; Shiva, M. P. (Indian Forester, 1988)
Pines have been commercially tapped for resin by "Cup&Lip method" from the beginning of this century. Recently it has been noticed that considerable damage to the growth and the timber of the pine trees is caused by resin tapping. To solve this problem a new method of tapping called "Rill method" was suggested/evolved by Dr. V.P.S. Verma the then Officer-in-Charge, M.F.P. Branch during the last decade. Studies were undertaken at F.R.I., Dehra Dun to compare the healing rate of blazes tapped by Cup&Lip method and "Rill method" in Pinus roxburghii. The studies revealed that while the rate of healing of blazes made by Rill method ranged from 19.2 to 51.3 cm2 per year in the case of Cup & Lip method it was from 4.8 to 12.2 cm2 per year.